ANALISIS CAPITAL EXPENDITURE - Asteria, Beta (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
This research uses panel data which is a combination of time series data and cross section data. Time series data for 3 years, from 2016-2018. As well as cross section data of 27 districts / cities. Incomplete data, no data on Revenue Sharing Funds are Indramayu District and Bekasi City. So that the cross section data used in the study were 25 districts/ cities. The number of observations (n) is 75. Source of data comes from the Directorate General of Fiscal Balance. The data used is the data on the realization of the West Java Regional Budget. The results of the research based on the t test prove that only the Regional Original Income variable partially has a significant effect on capital expenditures in regencies/ cities in West Java. Meanwhile, the General Allocation Fund, the Special Allocation Fund and the Profit Sharing Fund partially have no effect on Regional Original Income. The F test proves that the Regional Original Income, the General Allocation Fund the Special Allocation Fund and the Revenue Sharing Fund simultaneously have an effect on Regency/ City Capital Expenditures in West Java. The result of the coefficient of determination (Ajd R2) is 0.772. This means that Regional Original Income, General Allocation Fund, Special Allocation Fund and Share Fund are able to explain the variability of Capital Expenditure of 77.20 percent, the remaining 22.8 percent is explained by other variables outside the model. It can be concluded that Regency / City Capital Expenditures in West Java rely on Regional Original Income